ANALISIS YURIDIS TERHADAP SENGKETA TANAH TNI AU, CQ LANUD SUWONDO YANG DIKUASAI OLEH MASYARAKAT SARIREJO (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 229.K/PDT/1991) - MAKMUR SIAHAAN (PREMISE LAW JURNAL, 2018)
Dispute in land at the area of 260 ha between TNI AU, in this instance, Lanud Suwondo and tillers at Kelurahan Sari Rejo, Medan Polonia Subdistrict, has not yet settled. Each party claims that they control the land so that they are in conflict. The research used juridical normative method by analyzing legal provisions such as UUPA No. 5/1960, PP No. 24/1997 on Land registration, and the Supreme Court’s Ruling No. 229.K/PDT/1991. The nature of the research was descriptive analytic by describing and analyzing the research problems and finding the correct answers as their solution. The legal consequence of the Supreme Court’s Ruling No. 229.K/Pdt/1991on both the conflicting parties is that TNI AU, in this instance, Lanud Suwondo is required to comply with the Supreme Court’s Ruling No. 229.K/Pdt/1991 which has accepted the claim of 87 plaintiffs for the tillers by handing in the land at the area of 5.6 hectares to the 87 tillers.Keywords: Land Dispute, TNI AU, in this Instance, Lanud Suwondo, Tillers, Kelurahan Sari Rejo